Filled trivacant icosahedra as building fragments in 17-atom endohedral germanides [TM2@Ge17]n− (TM = Co, Ni). Issue 39 (27th September 2021) - Wallach, Christoph; Selic, Yasmin; Witzel, Benedikt J. L.; Klein, Wilhelm; Fässler, Thomas F.
Abstract : Endohedral germanides [ TM 2 @Ge17 ] n − ( TM = Co, Ni) comprising structure motifs of twelve-atom icosahedral clusters mark intermediates for cluster growth mechanisms. Abstract : The syntheses and the characterization of two 17-atom endohedral Ge clusters, [Co2 @Ge17 ] 6− (1a ) and [Ni2 @Ge17 ] 4− (2a ), are reported. The anions 1a and 2a, which close the gap between the known 16- and 18-atom Ge clusters, are investigated by single crystal X-ray diffraction and by quantum chemical calculations. The structures mark a new example on the pathway for cluster growth towards larger clusters with icosahedral symmetry. Furthermore, the [Co@Ge10 ] 3− anion (3a ) is obtained from liquid ammonia.